PSYCHOLOGICAL RESOURCE FOR PROFESSIONAL DEVELOPMENT AND SUCCESSFUL PROFESSIONAL SELF-FULFILLMENT OF FUTURE SPECIALISTS IN THE HUMAN-TO-HUMAN OCCUPATIONS (Psychology Travelogs, 2024)
The article emphasizes the need for the development of such a psychological resource of professional development and successful professional self-realization of future specialists in "human-to-human" professions as social maturity.It was found that the basic, fundamental components of this phenomenon are: first, responsibility, tolerance, self-development and an integrative component, which is positive thinking, a positive attitude towards the world.The features of the basic components of social maturity as a psychological resource for the formation of specialists in the socionomic profile have been revealed. The formation of responsibility is directly determined by giving the individual freedom in decision-making. The formation of responsibility is connected with the development of personal autonomy and ensuring the freedom of decision-making regarding oneself.It is emphasized that the need for self-development, self-actualization is a significant component of a mature personality. In the structure of the general phenomenon of tolerance, two types can be distinguished: sensual tolerance of the individual and dispositional tolerance of the individual. In the dispositional tolerance of the individual, an integral formative factor - a positive attitude towards the world - is quite clearly manifested.The use of a number of strategies for the development of psychological resourcefulness in future specialists is proposed, among which the priority is training on emotional intelligence (exercises on recognizing and managing emotions, empathy, social skills); stress reduction programs (relaxation techniques, time planning, relaxation exercises); reflection classes (exercises of self-awareness, self-analysis, imagining the future); motivational programs (goal-setting exercises, self-motivation, career planning).
Keywords: professional formation; professional development and self-development; professional self-realization; future specialists of the; psychological resource; resourcefulness; resourcefulness strategies